(untitled) (Conferencea, 2023)
The article interprets such topics as the problems and problems that students face in the process of learning this subject, the transfer of new technologies and teaching methods to the educational process. Nowadays, it is appropriate to explain the importance of computer science and information technology to students and how they learn through charity events, textbooks and educational tools. The article also discusses the challenges in preparing students for this subject, how they relate to effective data use, and the importance of guidance and support for teachers and schools. The article is written on the basis of common international experiences, research and insights, and provides information on the current situation and the expansion of education.